Analisis Sistem Pengendalian Internal Pengelolaan Dana BOS pada SDN Waru 03 - Inaya, Fadia; Zakaria, Adam; Prihatni, Rida (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the management of BOS Funds at SDN Waru 03, which includes the planning, implementation, and evaluation stages. The analysis is conducted based on five components in the Government Internal Control System (SPIP), namely the control environment, risk assessment, control activities, information and communication, and monitoring. The method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data validity is obtained through technical triangulation. The results of the study indicate that the management of BOS funds has been running quite well and in accordance with SPIP principles. However, several obstacles are still found such as an imbalance in human resource competencies, limited facilities, weak external coordination, and the absence of written SOPs. Therefore, it is necessary to increase human resource capacity, optimize facilities, prepare SOPs, and strengthen cooperation with external parties through forums or regular consultations.